Pengembangan Gim Edukasi Kebersihan Lingkungan untuk Kesadaran Masyarakat Akibat Pencemaran: Indonesia - Zefanya, Marcellino; Dirgantara, HB (UNIVERSITAS KALBIS, 2025)
The purpose of this research is to develop a educational game with game maker game engine as an alternative media for general public awareness, researchers take a material model that will be applied to 2D games and platformers. The method used by researchers is the Game Development Life Cycle (GDLC) method with stages: initiation, pre-production, production, black box testing, beta, and release. The final result of this research is an educational game entitled